2017
DOI: 10.1055/s-0037-1604180
|View full text |Cite|
|
Sign up to set email alerts
|

Physical Activity during Pregnancy: Recommendations and Assessment Tools

Abstract: The literature that supports and recommends the practice of exercise during pregnancy is extensive.However, although a more complete research on ways to evaluate the physical activity performed by pregnant women has been perfomed, it is found that there is no gold standard and that the articles in the area are inconclusive. Thus, the objective of the present article is to review relevant aspects, such as, technique and applicability of the different methods for the assessment of physical activity during pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 72 publications
(184 reference statements)
1
14
0
2
Order By: Relevance
“…It is intriguing that we find similar phenotypes monitoring wrist actigraphy in women and wheel running in mice. Suppression of general activity during pregnancy has been reported in women using questionnaires, pedometry, and actigraphy (Shima, 1990; Sternfeld, 1997; Lindseth and Vari, 2005; Cioffi et al, 2010; Harrison et al, 2011; Nascimento et al, 2015; Oliveira et al, 2017) and in mice using general activity and wheel running (Richards, 1966; Terada, 1974; Albers et al, 1981; Rosenwasser et al, 1987; Scribner and Wynne-Edwards, 1994; Ducsay, 1996). We conclude that noninvasive methods such as actigraphy can be used to study how chronotype disruption, including shift work, might affect reproductive and delivery outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing that we find similar phenotypes monitoring wrist actigraphy in women and wheel running in mice. Suppression of general activity during pregnancy has been reported in women using questionnaires, pedometry, and actigraphy (Shima, 1990; Sternfeld, 1997; Lindseth and Vari, 2005; Cioffi et al, 2010; Harrison et al, 2011; Nascimento et al, 2015; Oliveira et al, 2017) and in mice using general activity and wheel running (Richards, 1966; Terada, 1974; Albers et al, 1981; Rosenwasser et al, 1987; Scribner and Wynne-Edwards, 1994; Ducsay, 1996). We conclude that noninvasive methods such as actigraphy can be used to study how chronotype disruption, including shift work, might affect reproductive and delivery outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, pregnant women who perform a physical activity more than twice a week for more than 20 min were considered fit (index two). To sum up, three categorical variables were calculated based on physical activity index score: Index 2(Fit), Index 1 (Active), and Index 0 (Not fit) (see Supplementary file 2) [32].…”
Section: Variables and Measuresmentioning
confidence: 99%
“…Regular physical activity (PA) is beneficial for health at all life stages [1][2][3]. Many studies, including several reviews and meta-analyses, have confirmed physical and emotional benefits during pregnancy [3][4][5][6][7][8], while the risks are scarce [9]. PA helps to avoid excessive weight gain during pregnancy, which additionally decreases the risks of comorbidities, such as gestational diabetes [3,[10][11][12], macrosomia [7,13], preeclampsia [8,14], and assisted or caesarean delivery [15][16][17].…”
Section: Physical Activity During Pregnancy: On Guidelines Performanmentioning
confidence: 99%